Paquidermodactilia transgressiva: relato de um caso Transgrediens pachydermodactyly: report of a case - Lia Rachel Gomes do Vale (Anais Brasileiros de Dermatologia, 2009)
A paquidermodactilia é forma rara de fibromatose digital envolvendo as porções proximais dos dedos, que afeta homens jovens. Apresenta-se caso de paciente de 25 anos com quadro de nódulos assintomáticos nas mãos há dois anos, e há três meses com lesões semelhantes nos pés e no joelho direito. O exame histopatológico revelou espessamento da derme com proliferação de fibroblastos e de fibras colágenas e aumento de mucina. O caso descrito corresponde à paquidermodactilia do tipo transgressiva. Pachydermodactyly is a rare form of digital fibromatosis involving the proximal portions of the fingers that usually affects young males. We present a 25-year-old male patient with a twoyear history of asymptomatic nodules in the fingers. Three months before the visit, he had observed similar lesions on the feet and right knee. Histopathological analysis showed thickened dermis with proliferation of fibroblasts and collagenous fibers, with deposition of mucinous material. This represents a rare case of pachydermodactyly of transgrediens form.